Editorial - Hayes, Grahame (PINS-Psychology in Society, 2026)
As we approach the point of celebrating one year's worth of democracy we have much to be joyous about. There is still a sense of incredulity when one thinks of the changes that have taken place since April 1994. One is tempted to bask in the glory of the "death of apartheid", and the birth of the "new, democratic, and non-racial" South Africa. However, democracy is not given to a people, a nation, a country, but rather has to be fought for, defended, and developed. It seems that this is as true for the society as a whole, as it is for social institutions, social groupings, organs of civil society, that make up the social totality. In other words, we, individually and collectivity, and in our collectivities, have a responsibility to develop and entrench democratic practices in all the interstices of social life.